Digital transformation of maritime transport: blockchain for the European single window - Martínez Boada, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
We live in a world where new technologies facilitate work within many key sectors. Regulation (EU) 2019/1239 establishes a single window in Europe to facilitate the exchange of information between port authorities and Member States, however, this model brings with it challenges related to the security, efficiency and interoperability of the system. In this context, Blockchain appears as an alternative capable of improving the transparency, security and efficiency of this single window, as it allows data to be recorded in an immutable way and information to be exchanged in real time and without borders. In addition, through the automation provided by Smart Contracts, human intervention can be reduced and the system made much more effective, helping the maritime sector to move towards a more efficient and safe future.